Proof of concept of a "greener" protein purification/enrichment method based on carboxylate-terminated carbosilane dendrimer-protein interactions - González-García, Estefanía; Maly, Marek; de la Mata, Francisco Javier; Gómez, Rafael; Marina, María Luisa; García, María Concepción (Analytical and bioanalytical chemistry, 2016)
Protein sample preparation is a critical and an unsustainable step since it involves the use of tedious methods that usually require high amount of solvents. The development of new materials offers additional opportunities in protein sample preparation. This work explores, for the first time, the potential application of carboxylate-terminated carbosilane dendrimers to the purification/enrichment of proteins. Studies on dendrimer binding to proteins, based on protein fluorescence intensity and emission wavelengths measurements, demonstrated the interaction between carboxylate-terminated carbosilane dendrimers and proteins at all tested pH levels. Interactions were greatly affected by the protein itself, pH, and dendrimer concentration and generation. Especially interesting was the interaction at acidic pH since it resulted in a significant protein precipitation. Dendrimer-protein interactions were modeled observing stable complexes for all proteins. Carboxylate-terminated carbosilane dendrimers at acidic pH were successfully used in the purification/enrichment of proteins extracted from a complex sample. Graphical Abstract Images showing the growing turbidity of solutions containing a mixture of proteins (lysozyme, myoglobin, and BSA) at different protein:dendrimer ratios (1:0, 1:1, 1:8, and 1:20) at acidic pH and SDS-PAGE profiles of the corresponsing supernatants. Comparison of SDS-PAGE profiles for the pellets obtained during the purification of proteins present in a complex sample using a conventional "no-clean" method based on acetone precipitation and the proposed "greener" method using carboxylate-terminated carbosilane dendrimer at a 1:20 protein:dendrimer ratio.
Keywords: Computer modeling; slivoň švestka; Protein Structure, Secondary; Protein Binding; Protein sample preparation; Carboxylic Acids; Dendrimers; silany; myoglobin; Solvents; Molecular dynamics; kyseliny karboxylové; sekundární struktura proteinů; rozpouštědla; simulace molekulární dynamiky; Carboxylate-terminated carbosilane dendrimers; Seeds; Molecular Dynamics Simulation; rostlinné proteiny; Fluorescence quenching; vazba proteinů; Hydrogen-Ion Concentration; dendrimery; sérový albumin hovězí; Plant Proteins; Muramidase; Silanes; Serum Albumin, Bovine; Prunus domestica; Myoglobin; koncentrace vodíkových iontů; muramidasa; chemická precipitace; Protein-dendrimer interaction; Chemical Precipitation; semena rostlinná